2021
DOI: 10.3389/fneur.2021.655746
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Correlates of Depression in Retired Elite Level Rugby League Players

Abstract: Background: There is considerable interest in determining whether later-in-life depression is associated with lifetime history of concussions or the duration of a career in professional contact and collision sports. Rugby league is a high-intensity collision sport involving a large number of tackles per game and a high rate of concussions. We examined predictors and correlates of depression in retired elite level rugby league players in Australia.Methods: Retired elite level rugby league players (N = 141, age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 115 publications
1
28
0
Order By: Relevance
“…By examining the increase in variance explained across all possible models, this method allows for comparing the additional contribution of each predictor to equivalent subsets of models (e.g., X 1 added to model X 2 + X 3 , X 2 added to model X 1 + X 3 , X 3 added to X 1 + X 2 ). Given the high correlation between comorbid contributing factors (Brett et al, 2021; Esopenko et al, 2017; Iverson, Van Patten, et al, 2021; Kerr et al, 2012; Schwenk et al, 2007), this method is advantageous in determining unique contribution of these factors to levels of subjectively rated cognition, as one factor’s additional contribution to the outcome could drastically differ depending on which other variables are included in the model; as well as the fact that a one-unit increase in one factor can simultaneously influence the outcome directly and indirectly through an increase in another factor (increase in pain can simultaneously increase depression, both acting on the outcome).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…By examining the increase in variance explained across all possible models, this method allows for comparing the additional contribution of each predictor to equivalent subsets of models (e.g., X 1 added to model X 2 + X 3 , X 2 added to model X 1 + X 3 , X 3 added to X 1 + X 2 ). Given the high correlation between comorbid contributing factors (Brett et al, 2021; Esopenko et al, 2017; Iverson, Van Patten, et al, 2021; Kerr et al, 2012; Schwenk et al, 2007), this method is advantageous in determining unique contribution of these factors to levels of subjectively rated cognition, as one factor’s additional contribution to the outcome could drastically differ depending on which other variables are included in the model; as well as the fact that a one-unit increase in one factor can simultaneously influence the outcome directly and indirectly through an increase in another factor (increase in pain can simultaneously increase depression, both acting on the outcome).…”
Section: Methodsmentioning
confidence: 99%
“…Higher levels of SCD have been observed among former contact sport athletes (Alosco, M.L., Kasimis, A.B., Stamm, J.M., Chua, A.S., Baugh, C.M., Daneshvar, D.H., Robbins, C.A., Mariani, M., Hayden, J., Conneely, S., Au, R., Torres, A., McClean, M.D., McKee, A.C., Cantu, R.C., Mez, J., Nowinski, C.J., Martin, B.M., Chaisson, C.E., Tripodis, Y., & Stern, R.A. et al, 2017; Esopenko et al, 2017). However, other health, mood, and lifestyle factors are also commonly present, often co-occurring, among former contact sport athletes as well (Brett et al, 2021; Esopenko et al, 2017; Iverson et al, 2021; Kerr et al, 2012; Prien et al, 2020; Schwenk et al, 2007). For example, interrelated relationships between pain, depression, and chronic sleep disturbance, have been observed in former elite-level contact sport athletes (Brett et al, 2021; Iverson, Van Patten, et al, 2021; Schwenk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Legend -Green repres ents a l a rge correl a tion (.5-1.0); Yel l ow repres ents a modera te correl a tion (.3-.5) rugby players who had clinically mild stress, anxiety, and depression (Iverson et al, 2021). A recent Canadian study also found non-athletes with persistent symptoms to have clinical levels of anxiety and depression, but they did not calculate the stress subgroup score (Doroszkiewicz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%